Calculating Depreciation of Fixed Assets Using the Straight Line Method (Case Study in Household Scale Hatchery (HSRT) Grouper Fish in Pasir Putih Village, Bungatan District, Situbondo Regency) - Musyaffa Rafiqie (Faculty of Science and Technology University Ibrahimy, 2019)
The purpose of the research is to describe, know and understand the value of depreciation fixed assets with Straight line method. At the Household Scale Hatchery (HSRT) grouper fish, village Pasirputih, Bungatan, Situbondo City. Qualitative research methods, descriptive type. The data collected is primary and secondary data. Respondents are taken by purposive sampling in which respondents are taken based on certain criteria. To calculate depreciation of fixed assets and their impact on profits, the Straight Line method is used. The size of the larvae is between 2.5 x 2 x 1.3 m to 4 x 2.5 x 1.8 m, like grading 2.5 x 2 x 1.5 to 3 x 2 x 1.5 m, like a palnton 1.5 x 1.5 x 1 m up to 3 x 2.5 x 1.8 m, rotifer tanks 1.5 x 1.5 x 1 up to 2.5 x 2 x 1.5 m and tanks of size 3 x 3 x 1.8 m up to 4 x 2.5 x 2 m. Fish that are turned over at household scale seedlings (HSRT), in Pasirputih Village, Bungatan District, Situbondo Regency are groupers. Farmers during HSRT operations, have never calculated depreciation of their HSRT infrastructure.